Bilateral alveolar rhabdomyosarcoma of breast: a rare entity - Varshney, Bharti (BMJ Case Rep, 2021)
Sarcomas of breast constitute less than 1% of all malignant breast tumours. Alveolar rhabdomyosarcoma (RMS) is very rare in breast with limited case reports in literature, and primary alveolar RMS arising from breast is still less common than metastatic RMS. Here, we report a case of primary bilateral alveolar RMS of breast in an adolescent female where the correct diagnosis was obfuscated by an overlap in the histological features of RMS and high-grade invasive ductal carcinoma.